Boosting pseudocapacity by assembling few-layer WS2 into mesoporous nanofibers towards high-performance anode. (10th June 2020) - Wan, Jia; Chen, Qinqin; Li, Wang; Pan, Linhai; Zhao, Zehua; Yu, Dongdong; Tang, Zhihong; He, Haiyong
Abstract: Transition metal dichalcogenides (TMDs) have shown potential as anodes in lithium-ion batteries (LIBs) due to high specific capacity. However, low conductivity and long diffusion distance in layered structure limited their electrochemical performance. Here, a feasible method was reported to assemble few-layer WS2 into mesoporous structure using carbon as a glue to create plenteous pseudocapacitive sites. In this way, the contribution of pseudocapacity in electrochemical process was dramatically increased. As a result, the specific capacity of WS2 reached 754 mA h g −1 at 500 mA g −1 after 120 cycles, double of theoretical value. The rate capability is also improved due to the high speed of pseudocapacitive reaction. Thus, the retention of specific capacity is enhanced from 47.6% to 63.2%, as current density is increased from 0.1 to 2 A g −1 .